Exosomes isolated from IMMUNEPOTENT CRP, a hemoderivative, to accelerate diabetic wound healing - García Coronado, Paola Leonor; Franco Molina, Moisés Armides; Zárate Triviño, Diana Ginette; Hernández Martínez, Sara Paola; Castro Valenzuela, Beatriz Elena; Zapata Benavides, Pablo; Rodríguez Padilla, Cristina (Frontiers in Bioengineering and Biotechnology, 2024)
The increasing risk of amputation due to diabetic foot ulcer calls for new therapeutic options; for that, we determined the role of IMMUNEPOTENT CRP (ICRP) and its parts in the wound healing process of superficial wounds on diabetic BALB/c mice. A potency test was performed to confirm the batch of ICRP, then its parts were separated into pellet, supernatant, and exosomes, and another group loaded with insulin. Viability and scratch healing were assessed in NIH-3T3, HUVEC, and HACAT cell lines. Diabetes was induced with streptozotocin, and wounds were made by dissecting back skin. Treatments were topically applied, and closure was monitored; inflammatory cytokines in sera were also evaluated by flow cytometry, and histological analysis was performed by Masson's staining and immunohistochemistry for p-AKT, p-FOXO, p-P21, and p-TSC2. ICRP pellets and exosomes increased cellular viability, and exosomes and exosomes-insulin accelerated scratch healing in vitro. Exosome-insulin releases insulin constantly over time in vitro. In vivo, treatments accelerated wound closure, and better performance was observed in pellet, exosomes, and exosomes-insulin treatments. Best collagen expression was induced by ICRP. P-AKT and p-FOXO were overexpressed in healing tissues. Inflammatory cytokines were down-regulated by all treatments. In conclusion, IMMUNEPOTENT CRP components, especially exosomes, and the process of encapsulation of exosomes-insulin accelerating diabetic wound healing, enhancing cellular proliferation, collagen production and inflammation modulation through the phosphorylation of components of the AKT pathway.